The impact of epilepsy on preschool children and their families - Tanrıverdi, Müberra; Mutluay Karantay, Fatma; Tarakçı, Devrim; Güler, Serhat; İşcan, Akın (Academic Press Inc Elsevier Science, 2016)
This study investigated the possible presence of sensory-motor developmental impairments in preschool children with epilepsy and explored epilepsy impact on their activities and quality of life and on the stress load of their family. Study participants were children aged 2-6 years diagnosed with epilepsy without any other comorbidities (epionly children). The instruments used for assessment included the Neurological, Sensory, Motor, Developmental Assessment (NSMDA) scale for sensory-motor development, the Impact of Childhood Neurologic Disability Scale (ICNDS), and the Impact of Pediatric Epilepsy Scale (IPES) for disease impact on disability and Quality of Life (QoL), as well as the Pediatric Outcomes Data Collection Instrument (PODCI) for functional health status, and the Parental Stress Scale (PSS) for the family stress load. Required data were obtained from direct testing or observation of children's activities and mother-supplied answers to questions. Eighty-two children were investigated. The NSMDA scores were in the normal development range 6-8. Significant moderate impact of the disease on disability and QoL was estimated with the ICNDS and IPES instruments. The PODCI scores were similar to healthy population levels except for the happiness dimension which was better for children with epilepsy. PSS were significantly above normal. The functional health and QoL of the children as well as their family stress were found to be positively correlated with increasing age. It is found that epilepsy does not degrade neuromotor development and functional health status of preschool epionly children, though it has a significant impact on their neurological disability and QoL and the stress level of their families; this impact seems to decrease with age.
WOS: 000384392500002
PubMed ID: 27428870
Keywords: Epilepsy; Neuromotor Development; Quality of Life; Parental Stress